Virtual Buzzwire: assessment of a prototype VR game for stroke rehabilitation - Christou, Chris; Michael-Grigoriou, Despina; Sokratous, Dimitris (My University, 2018)
We created a VR version of the Buzzwire children’s toy as part of a project to develop tools for assessment and rehabilitation of upper-body motor skills for people with dexterity impairment after stroke. In two pilot studies, participants wearing a HMD used a hand-held wand with precision tracking to traverse virtual ‘wires’. In the first study, we compared able-bodied participant’s performance with and without binocular viewing to establish a connection with previous experiments using physical versions of the game. Furthermore, we show that our extended measures were could also discern differences between subjects’ dominant versus non-dominant hand. In a second study, we assessed the usability of the system on a small sample of subjects with post-stroke hemiparesis. There was positive acceptance of the technology with no fatigue or nausea and measurements highlighted the differences between the hemiparetic and unaffected hand.
Keywords: Patient rehabilitation; Games; Virtual reality; Binocular viewing; Stroke rehabilitation